Penerapan Analisa Resiko Keamanan Informasi Pada Layanan Aplikasi PKK Kecamatan Kembangan: Wujudkan Jakarta Tangguh dan Berdaya Saing - Yusuf, Mohamad; Awang, Nungky; Sabily, Inna (Education and Talent Development Center of Indonesia, 2025)
In the era of digital transformation, public services such as PPK (District Election Committee) Kembangan in Jakarta are not exempt from information security challenges. This digital transformation involves integrating advanced technology into daily operations and providing services to the public through digital platforms. As the use of digital systems increases, so does the risk of cyberattacks. PPK Kembangan may face attacks such as phishing, ransomware, denial-of-service attacks, or misuse of citizens' personal data, which could disrupt election processes or other district activities. To enhance prevention against threats and vulnerabilities in information security within PPK Kembangan’s application services, a community service program was conducted through training for PPK Kembangan members. The results of this program showed that the training was successful, with participants demonstrating high enthusiasm. Participants actively asked questions regarding cases of information security attacks on both web-based and mobile applications. This program is expected to increase awareness of preventing cyber threats and vulnerabilities in PPK Kembangan’s service applications, thereby minimizing the occurrence of such attacks.